Inward Rectifier Potassium Channels: Membrane Lipid-Dependent Mechanosensitive Gates in Brain Vascular Cells - Sancho, Maria; Fletcher, Jacob; Welsh, Donald G. (Frontiers in Cardiovascular Medicine, 2022)
Cerebral arteries contain two primary and interacting cell types, smooth muscle (SMCs) and endothelial cells (ECs), which are each capable of sensing particular hemodynamic forces to set basal tone and brain perfusion. These biomechanical stimuli help confer tone within arterial networks upon which local neurovascular stimuli function. Tone development is intimately tied to arterial membrane potential (VM) and the changes in intracellular [Ca2+] driven by voltage-gated Ca2+ channels (VGCCs). Arterial VM is in turn set by the dynamic interplay among ion channel species, the strongly inward rectifying K+ (Kir) channel being of special interest. Kir2 channels possess a unique biophysical signature in that they strongly rectify, display negative slope conductance, respond to elevated extracellular K+ and are blocked by micromolar Ba2+. While functional Kir2 channels are expressed in both smooth muscle and endothelium, they lack classic regulatory control, thus are often viewed as a simple background conductance. Recent literature has provided new insight, with two membrane lipids, phosphatidylinositol 4,5-bisphosphate (PIP2) and cholesterol, noted to 1) stabilize Kir2 channels in a preferred open or closed state respectively, and 2) confer, in association with the cytoskeleton, caveolin-1 (Cav1) and syntrophin, hemodynamic sensitivity. It is these aspects of vascular Kir2 channels that will be the primary focus of this review.